UPAYA-UPAYA PETANI PADI SEKITAR DAERAH PARIWISATA PANGANDARAN DI ERA COVID-19 (Studi Kasus Desa Cibenda, Kecamatan Parigi, Kabupaten Pangandaran) - Ai Sri Hartati; Yayat Sukayat (Universitas Galuh Ciamis, 2021)
Tourism has a significant share in the contribution of the country's economy, tourism contributes to the national Gross Domestic Product (GDP). The covid-19 pandemic has forced all tourism in Indonesia to be closed to avoid the spread of the corona virus. The closure of tourism was carried out by the Pangandaran Regency government, this effort was made to anticipate the spread of the corona virus in Pangandaran Regency. The research objective was to determine the effect of covid-19 on rice farmers around the Pangandaran tourism area and to determine the efforts of rice farmers around the Pangandaran tourism area in the covid-19 era. The research design used is descriptive qualitative with a case study approach. Retrieval of data using the interview method directly to informants. The results showed that Covid-19 had an effect on rice farmers around the Pangandaran tourism area. In rice farming, farmers experience the greatest influence on labor, distribution of fertilizer and rice marketing, this is because hotels, restaurants and restaurants are closed, resulting in difficulties in marketing rice. With this influence, farmers make several efforts to meet their daily needs. The efforts of rice farmers around the Pangandaran tourism area in the Covid-19 era are efforts made by the government and efforts made by the farmers themselves. Efforts made by the government 1) direct cash assistance, 2) basic food assistance and efforts made by the farmers themselves, namely 1) reduction of labor, 2) using family labor, 3) reducing fertilizer doses, 4) borrow moneyfrom neighbors or non-banks, 5) reducing rice sales, 6) planting other crops with reduced sales volume.